2019
DOI: 10.1186/s12862-019-1457-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-specific evolutionary patterns of antimicrobial-resistant Salmonella enterica

Abstract: Background The emergence of antimicrobial-resistant (AMR) strains of the important human and animal pathogen Salmonella enterica poses a growing threat to public health. Here, we studied the genome-wide evolution of 90 S. enterica AMR isolates, representing one host adapted serotype ( S. Dublin) and two broad host range serotypes ( S. Newport and S. Typhimurium). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 115 publications
(153 reference statements)
2
22
0
Order By: Relevance
“…Such geographic association of lineages was suggested to 536 be caused by differences in prophage regions, pathogenicity islands and fimbrial operons among 537 strains from different geographic locations (Zheng et al, 2017). AMR S. Newport analyzed here 538 belong to Lineage IIC as previously reported by Liao et al (2019). Our findings suggest that within 539 this lineage, S. Newport also has a geographic structure at the SNP level.…”
Section: Identification Of Host Associated Genes and Pseudogenes Encosupporting
confidence: 69%
“…Such geographic association of lineages was suggested to 536 be caused by differences in prophage regions, pathogenicity islands and fimbrial operons among 537 strains from different geographic locations (Zheng et al, 2017). AMR S. Newport analyzed here 538 belong to Lineage IIC as previously reported by Liao et al (2019). Our findings suggest that within 539 this lineage, S. Newport also has a geographic structure at the SNP level.…”
Section: Identification Of Host Associated Genes and Pseudogenes Encosupporting
confidence: 69%
“…Genome sequence data for all 90 isolates have previously been reported (Carroll et al, 2017) and deposited in the National Center for Biotechnology Information's (NCBI) Sequence Read Archive under accession number SRP068320. Genome assembly has also been reported previously (Carroll et al, 2017, Liao et al, 2019 and assembled genomes are available at NCBI DDBJ/ENA/ GenBank under the accession numbers listed in Supporting Table S4 in Liao et al (2019). Previously reported data (Liao et al, 2019) for (i) genome annotation including identification of pseudogenes by NCBI Prokaryotic Genome Annotation Pipeline (Tatusova et al, 2016), (ii) identification of orthologous genes (non-pseudogenes) by OrthoMCL (Li et al, 2003), (iii) assignment of gene ontology (GO) and enzyme commission (EC) terms by Blast2GO v1.2.1 (Conesa et al 2005), and (iv) highquality core single-nucleotide polymorphisms (SNPs) for S. Dublin, S. Newport, and S. Typhimurium called by Cortex variant caller (Iqbal et al, 2012) were used here.…”
Section: Isolates and Whole Genome Sequence Datamentioning
confidence: 84%
“…The emergence of AMR strains has been described for all three serotypes (Foley and Lynne, 2008). In our previous study of AMR S. Typhimurium, S. Newport and S. Dublin isolated from human and bovine sources in New York state (NY) and Washington state (WA), we found that it is likely that antimicrobial resistance has emerged independently in multiple S. Typhimurium lineages, as compared to single lineages of S. Newport and S. Dublin (Liao et al, 2019). Also, our initial study of these isolates revealed a strong source and geographic association with antimicrobial resistance (Carroll et al, 2017).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations